1993
DOI: 10.1002/hep.1840180516
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative measurement of segmental liver volume of donors for living related liver transplantation

Abstract: Segmental liver volume determination by computed tomographic scan was carried out preoperatively in nine donors for living related liver transplantation. The calculated volume was compared with the graft size actually obtained by three types of donor hepatectomy. The volume of the left lateral segment (175 to 241 ml) and the left lobe (310 to 490 ml) varied markedly among the donors. The ratio of the left lobar to total liver volume also showed a wide range of values (23.2% to 35.9%). The value of the left lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
1
8

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 16 publications
2
125
1
8
Order By: Relevance
“…After segmentation, the total liver surface was generated automatically and partitioned into its segments of individual portal venous supply with the segmental volumes being calculated automatically. In accordance with the literature [19], we found a large variance between the volumes of liver segments. In our study, volumes ranged from 760 to 1770 ml for the right lobe, 330 to 760 ml for the left lobe and 190 to 410 ml for the left lateral segments II+III.…”
Section: Graft Size and Volumetric Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…After segmentation, the total liver surface was generated automatically and partitioned into its segments of individual portal venous supply with the segmental volumes being calculated automatically. In accordance with the literature [19], we found a large variance between the volumes of liver segments. In our study, volumes ranged from 760 to 1770 ml for the right lobe, 330 to 760 ml for the left lobe and 190 to 410 ml for the left lateral segments II+III.…”
Section: Graft Size and Volumetric Analysissupporting
confidence: 93%
“…Other studies reported in the current literature show acceptable correlations between estimated and measured liver volume as well [4,13,19,20]. Closer analysis of these studies showed differing deviations, such as systematic underestimation of left-lobe volume [19] and a high variance of the measurements [13,20].…”
Section: Graft Size and Volumetric Analysismentioning
confidence: 60%
“…In these cases, accurate measurements of segmental liver volumes are important for both the donor and recipient. In a small study of living related donors, the volume of left lobe segments measured by CT correlated strongly with the actual volumes of the transplanted graft [4].…”
Section: Discussionmentioning
confidence: 96%
“…The liver is one organ where numerCorrespondence to: K. K. Kopecky ous attempts have been made to employ imaging techniques to make quantitative volumetric measurements. Measurements of liver volume have been used to make surgical decisions regarding hepatic resection or transplantation, to plan radiotherapy dosimetry, to assess the progress of various diseases, and to assess responses to treatment [1][2][3][4][5][6][7][8][9][10][11]. Most of the studies to date have been performed with conventional computed tomography (CT) after intravenous administration of iodinated contrast material, and some were performed after intra-arterial administration of iodinated contrast material (CT arterial portography).…”
mentioning
confidence: 99%
“…In the first technique, the use of cross-imaging techniques can precisely determine the volume of liver tumors and liver mass [86]. The actual liver volume can be calculated with CT or MRI imaging techniques, on each slice both TLV and FRL are outlined, and the sum of the slices are calculated with integrated software [87]. Tumor volumes are considered nonfunctional liver parenchyma and subtracted from TLV [84,88].…”
Section: Limits For Safe Liver Resectionmentioning
confidence: 99%